Analysis of Heat Transfer in The VVER-1200 Reactor’s Heat Channel - Dinh Van, Thin; Bui, Loat Van; Bui, Hong Thi (VNU Journal of Science: Mathematics - Physics, 2017)
In early 2015, the Government of Vietname has decided to choose VVER-1200 Russian-made technology for building at the Nuclear Power Plant in Ninh Thuan 1, this is the advanced reactor generation III + and the only one has been completed for the first time in the world in August 2016. Vietnam is facing a major challenge, which is how to ensure the acquired technology transfer process, then the safe operation of thisunit. This article analyzes some of the heat changes occur in reactor when there are changes of the heatflux. This is an issue directly related to the workof predictingincidents and give ways to fix the problem when the plant is in conditions such as  startup, normal and abnormaloperations. For analysis, the authors used CFD methods, this is a very modern method and have high reliability. The results received have fit well when compared with the safety analysis report of Rosatom published.